Prognostic Value of Electrocardiographic Abnormalities and Troponin-I Elevation in Hospitalized COVID-19 Patients (Bangladesh Heart Journal, 2021)
Background: Corona Virus Disease (COVID -19) patients present mainly with respiratory manifestations and viral pneumonia. The cardiovascular presentation includes early signs of acute myocardial injury. Troponin elevation is a frequent laboratory finding in hospitalized patients with the disease, and may reflect direct vascular injury or nonspecific supply-demand imbalance. In this work, we assessed the correlation between different ranges of Troponin elevation, Electrocardiographic (ECG) abnormalities and mortality.Methods and materials: It was a prospective observational study, conducted in four tertiary care Private Hospitals of Chattogram City of Bangladesh. The study enrolled 181 consecutive patients admitted to hospital from June 01, 2020 to December 31, 2020 due to Covid-19 disease on the basis of presentation of signs and symptoms severity. Upon admission, routine investigations cTnI and ECG were carried out.Results: Mean age of the patients was 54.3±7.3 years with 63.5% male. Hypertension was the most common comorbidity followed by diabetes and obesity. 57.1% of the patients had abnormal ECG. Abnormal axis deviation [26 % (left axis deviation 23.9% vs right axis deviation 2.0%)], Poor R wave progression (22.9%), T inversion (14.5%), left ventricular hypertrophy (LVH) (11.4%) followed by ST segment depression (8.3%) were major findings observed in the study population. Presence of LVH (p=0.008), ST segment elevation (p≤0.001), ST segment depression (p≤0.001) and T inversion (p=0.003) showed statistically significant association with Severe COVID-19 disease. 48.2% had raised cTnI level. Thirteen (7.2%) patients expired in hospital. The mortality rate increased with incrementally higher troponin group: 12/18 than mildly elevated troponin 1/63 (p < 0.01). The presence of an abnormal ECG finding resulted in significant in the intermediate Troponin elevation group (0.05-1 ng/ml) but not in the low ( 1 ng/ml) Troponin elevation groups. There were statistically significant association between between cTnI level and death; and between ECG findings and death.Conclusion: Study conclude that Troponin-I level and ECG are a prognostic factor for mortality in hospitalized COVID-19 patients.Bangladesh Heart Journal 2021; 36(2): 105-112